Blood Flow Parameters of the Central Retinal and Internal Carotid Arteries in Asymmetric Diabetic Retinopathy - Morteza Mehdizadeh (Journal of Ophthalmic & Vision Research, 2012)
Purpose: To investigate the correlation between diabetic retinopathy severity and blood flow parameters in the central retinal artery (CRA) and internal carotid artery (ICA). Methods: This comparative study included 40 eyes of 20 patients with asymmetric diabetic retinopathy. Twelve subjects had asymmetric diabetic macular edema while eight patients had proliferative diabetic retinopathy (PDR) in one eye and non-proliferative diabetic retinopathy (NPDR) in the fellow eye. Bilateral color Doppler imaging (CDI) of the CRA and ICA was performed to determine resistance index (RI) and peak systolic velocity (PSV). RI and PSV values were compared between eyes with higher grades of macular edema (> 2 grades of difference with the fellow eye) and fellow eyes with less severe macular edema, as well as between eyes with PDR and fellow eyes with NPDR. Results: Mean RI of the CRA in eyes with higher grades of macular edema was 0.78±0.11 as compared to 0.69±0.08 in fellow eyes with less severe macular edema (P=0.012), while PSV of the CRA was 58.83±18.93 cm/s in eyes with higher grades of macular edema versus 59.75±11.83 cm/s in fellow eyes with less severe macular edema (P=1.00). Mean PSV of the ICA was 55±23.94 cm/s in eyes with PDR and 69.25±34.30 cm/s in eyes with NPDR (P=0.008) while mean RI of the ICA was 0.81±0.13 in eyes with PDR and 0.76±0.12 in eyes with NPDR (P=1.00). Conclusion: Evaluation of RI in the CRA and PSV in the ICA by CDI in diabetic patients may identify eyes at risk of more severe macular edema and PDR.